Shariah non-compliance treatment in Malaysian Islamic banks - Hassan, Rusni; Omar, Hani Nabila (New Millennium Discoveries, UK, 2019)
Islamic finance in Malaysia has been growing rapidly in the past 30 years. In 2019, there is a total of 16 Islamic banks listed and supervised by Bank Negara Malaysia (BNM), with 5 out 16 banks are foreign entities. In view of the rivalry with the conventional banking sector, Islamic banks offer new innovative Islamic products and financial projects which may lead to greater risk of Shariah Non-compliance (SNC) exposure to the Islamic Financial Institutions (IFIs) in its effort to stay competitive. This paper attempts to explore the current practices of Islamic banks in treating (SNC) and the extent of compliance with BNM rules and guidelines, particularly BNM Operational Risk Integrated Online Network (ORION) requirement on SNC reporting event. This paper adopts a qualitative research method by conducting semi-structured in-depth interview with the Islamic banking professionals targeting five Islamic banks. Both primary and secondary sources are used for data collection. The finding shows that these Islamic Banks adhere to the BNM rules and requirements, with some minor differences in the implementation process. The findings would contribute positively in terms of enriching and contributing to the existing literature on the SNC practices by Islamic Banks whilst at the same time establishing the levels of compliance of the banks under investigation.